The effect of a physical-motor program for the development of (endurance of muscle strength, lengthening of major muscle groups, balance and alignment) for children with mild motor disability (06-02 years) - Deghnouch , Okba; Lebad , Meamar (Social Empowerment Journal, 2021)
Perhaps each research has its own objectives, so our research aims mainly to find out the effect of a kinetic program for the development (endurance of muscle strength, lengthening of major muscle groups, balance and compatibility) for children with mild motor disabilities on the growth and acquisition of physical and motor abilities through the application of a raise the performance of physical, motor and perceptual capabilities. Given the results represented by the high level of muscle balance indicators after implementing the proposed training program, the researcher concluded the following: - Children with slight mobility disabilities are in urgent need of programs that develop (endurance of muscle strength, lengthening of major muscle groups, balance and compatibility) in order to improve the physical and motor level